(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this study is to determine whether or not participating in a game using image cards assists students in better recalling verb-related terminology. The nature of this research is experimental, and it is structured according to an A1-B-A2 design single subject research (SSR). Students in high school who fall somewhere on the autistic spectrum are taking part in the research. The performance tests, the observations, and the written documentation for data collection were all a part of the implementation of Baseline-1, the intervention, and Baseline-2 respectively. The participants will be asked to take a performance test based on their knowledge of vocabulary and verbs in order to collect information. The investigation revealed that students had a higher level of engagement in the classroom when utilizing the picture cards as well as during the intervention session. When there were no outside or internal distractions, they exhibited interest in what was being taught, asked questions, and paid careful attention to what was being presented to them. The subject’s proficiency in using verbs drawn from the lexicon has also shown signs of improvement. The outcomes of the research imply that instructing students with autism to play a game with picture cards may help them learn more words. Therefore, we are able to reach the conclusion that playing picture card games has an effect on broadening the pupils’ vocabulary via its use.